2019
DOI: 10.3390/medicina55100690
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Warm-Up Routine on the Ankle Injuries Prevention in Young Female Basketball Players: A Randomized Controlled Trial

Abstract: Background and Objectives: Ankle joint is the most common site of injury for basketball athletes. An effective warm-up (WU) is a period of preparatory exercise to improve training performance and reduce sports injuries. Continuous examination of effective WU routines in basketball players is a necessity. The aim of this study was to investigate the effects of general and combined warm up on ankle injury range of motion (ROM) and balance in young female basketball players. Materials and Methods: A sample of 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
1
17
0
4
Order By: Relevance
“…Both methods of indirect assessment ([CK] and DOMS) of the appearance of muscle damage are widely used, confirming their applicability in assessing the response to damage caused by eccentric exercise [28,29]. In the present study, the responses of [CK] and DOMS suggest that the protocol was similarly effective in inducing muscle damage in the two compared sessions.…”
Section: Discussionsupporting
confidence: 72%
“…Both methods of indirect assessment ([CK] and DOMS) of the appearance of muscle damage are widely used, confirming their applicability in assessing the response to damage caused by eccentric exercise [28,29]. In the present study, the responses of [CK] and DOMS suggest that the protocol was similarly effective in inducing muscle damage in the two compared sessions.…”
Section: Discussionsupporting
confidence: 72%
“…Looking at the mean age of patients in this study who sustained an ankle sprain (36 ± 16 years), one can assume that younger players are either more prone to sustain an ankle injury or rather play, compete, and run faster, which may facilitate an inversion ankle sprain. Regular preplay warm-up and stretching, as well as proprioceptive, neuromuscular, and exercise training, have been shown to reduce the risk of ankle sprains 3,14,16,26,31,35 and could be especially advised to the younger recreational players. However, the effectiveness of injury prevention programs in tennis remains questionable because it was recently shown that adult recreational tennis players did not reduce their ankle injury rate after an unsupervised tennis-specific exercise program.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized control trial, Padua et al found that NMT warm-up programs, which include aerobic, agility, balance, and strength exercises, lowered the risk of enduring an ankle sprain injury by 32% in adolescent female basketball players. 75 Additionally, plyometrics and exercises that drill rapid changes in direction mitigate losses in agility and endurance incurred during mandatory breaks in sports. 76 Furthermore, the efficacy of warm-up NMT programs when supervised only by coaches who received training on implementing these programs compared to physiotherapists produced similar results in a cluster-randomized trial on youth female soccer players.…”
Section: Do Warm-ups Matter?mentioning
confidence: 99%